UPAYA MENUMBUHKAN SELF-CONFIDENCE BERBICARA BAHASA ARAB MAHASISWA MELALUI GRUP WHATSAPP - Sa`diyah, Halimatus (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
This research study is focused on how efforts to foster self-confidence speak Arabic through Whatsapp groups in PKPBA UIN Maliki Malang? The purpose of the study is to describe efforts to foster self-confidence in PKPBA UIN Maliki Malang students in speaking Arabic through Whatsapp groups. The positive results that contributed to this research are positive things that can be used by educators in the use of WhatsApp group as an effort to foster confidence for students to speak Arabic, train students to dare to speak Arabic, and become one of the source of thought for speaking skills learning strategies in PKPBA UIN Maliki Malang. Based on the above objectives, this research is a qualitative type with data collection techniques: observation, and documentation. While the data is descriptive and analyzed inductively. From this research, a finding was found that self-confidence in students to speak Arabic can be grown with the use of Whatsapp groups.